Plea Bargaining in the United States, 1978 - Miller, Herbert S. ([Verlag nicht ermittelbar], 1984)
This study was conducted in 1978 at the Institute of Criminal Law and Procedure of the Georgetown University Law Center. The study consists of three files. The first contains information from 3,397 case files in six United States cities. The 63 variables include demographic information on the accused and the victim, past record of the accused, seriousness of the offense, pleas entered, speed of trial process, and sentencing. The second file contains information gathered from in-court observations focused on the formal supervision of plea bargaining by judges. There are approximately 33 variables for each of the 711 court observations. The third file consists of the results of a plea bargaining simulation game. There are 17 variables for each of the 479 cases in the file.